Kontribusi Gerakan Nurcu dalam Kebangkitan Islam di Turki - Akhmad Rizqon Khamami (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This paper discusses the contributions of Nurcu movement in strengthening Islam in contemporary Turkey. In consonance with the rising of Turkey as a strong country in political and economical sphere on global level, this country is said to be a symbol of Islamic renaisance of the Muslim world. The four consecutive victories of Erdo?an?s party in Turkey general election is seen as a solely factor for the Islamic renaisance of Turkey. But this writer argues that there is yet another Islamic movement which worked on Islamic da?wah far before AKP grabbed the power. Nurcu is that of this very Islamic movement. It has a large number of members ranged from businessmen, intellectuals, students, and housewives. The businessmen of Nurcu are known as ?Anatolian Tigers? who contribute in developing economy of Turkey since Turgut ?zal opening up liberal economy and integrating its economy into greater lap of the world economy in 1980s. This development of the Turkey economy walks hand in hand with spirit of Islamic way of life within Turkish people. This writer assumes that the movement has paved the way for AKP?s victories; and is currently for Recep Tayyip Erdo?an to receive the tittle of newly-found Islamic hero of the contemporary Islam in the Indonesian political Islamists? view.